Editorial - Pesambili, Joseph C. (Papers in Education and Development, 2024)
Dear readers, It is with immense pleasure that we welcome you back to Papers in Education and Development (PED), where we once again present to you Volume 41, Issue 2 of December 2023. As always, this issue delves into a vibrant tapestry of themes, trends, and experiences shaping the educational landscape across all levels of education and diverse educational sectors in sub-Saharan Africa. Arriving amidst a dynamic and ever-changing landscape of education throughout the world, this issue presents a stimulating collection of thoughtful and timely research-based papers tackling critical issues in education across diverse geographical settings in Africa. The issue is released in the context where many countries around the world are still grappling with the lingering effects of the post-COVID-19 era, navigating the complexities of technological integration and striving to ensure access to quality education for all. Overall, the 11 articles presented in this edition explore a kaleidoscope of thought-provoking themes and questions challenging us to critically examine the existing educational policies and practices, embrace innovative solutions, and work towards a better future for all.